UPAYA MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF SISWA DALAM MATA PELAJARAN IPA DI KELAS 5 - Sukaesih; Encep Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Creative thinking skills are essential for elementary school students to face the challenges of the rapidly advancing and increasingly complex 21st century. However, the low level of students' creative thinking abilities, especially in science learning, has become a pressing issue that requires immediate attention. This problem not only affects students' understanding of science concepts but also diminishes the meaning and effectiveness of learning. This study aims to identify the extent of students' creative thinking abilities in science learning and explore solutions to enhance these skills, making learning more meaningful and delivering optimal outcomes.